Merger simulation in mobile telephony in Portugal - Grzybowski, L.; Pereira, P. (Review of Industrial Organization, 2007)
This article assesses the unilateral effects on prices of a merger in the Portuguese mobile telephony market. We use aggregate quarterly data from 1999 to 2005 and a nested logit model to estimate the price elasticities of demand and the marginal costs of subscription of mobile telephony. Given these estimates, we simulate the effects of the merger. We find that the available mobile telephony subscription products are close substitutes. The merger may cause substantial price increases, even in the presence of large cost efficiencies. On average, prices increase by 7-10% without cost efficiencies, and by about 6-10% with a 10% marginal cost reduction.